Impact of digital technology on farmland transfer and food security: an empirical study in rural China - Guo, Xinyu; Liu, Xianghua; Lv, Jinwei; Zhu, Ruojia (Frontiers in Environmental Science, 2025)
By optimizing the mechanism of farmland transfer, digital technology promotes large-scale and mechanized operation, significantly improves agricultural production efficiency and resource utilization rate, which provides key support for ensuring food security. Using panel data of Rural Fixed Observation Point in Henan Province from 2009 to 2022, this study empirically investigates the impact of Internet access on farmland transfer and constructs a mathematical theoretical model to study the potential mechanism. This study finds that the Internet access of farmers can promote the transfer of farmland. The potential mechanisms are the resource reallocation effect triggered by increased non-farm employment and income, the efficiency-enhancing effect of agricultural production driven by digital technology, and the transaction facilitation effect brought about by lower information costs. Heterogeneity analysis shows that in terms of policy support, the increase of grain purchase price and direct subsidy positively regulate the willingness to transfer; In terms of farmers’ capital endowment, the groups with high human capital and physical capital are more inclined to transfer out of farmland, while the households with high land capital show the characteristics of farmland dependence, and the households with high information capital have a stronger willingness to transfer farmland; In terms of economic and cultural attributes, farmers located in agricultural areas, underdeveloped areas and traditional villages also have stronger willingness to transfer farmland. These findings not only help to release the potential of land factors but also provide a feasible path for small farmers to connect with modern agriculture through technology empowerment, which has dual practical value for ensuring food security and promoting rural revitalization.